Inflation and Welfare - Lucas, Jr., Robert E. (Econometrica, 2000)
This paper surveys research on the welfare cost of inflation. New estimates are provided, based on U.S. time series for 1900–94, interpreted in a variety of ways. It is estimated that the gain from reducing the annual inflation rate from 10 percent to zero is equivalent to an increase in real income of slightly less than one percent. Using aggregate evidence only, it may not be possible to estimate reliably the gains from reducing inflation further, to a rate consistent with zero nominal interest.